Integrasi Nilai Islam dan Lokalitas Budaya: Kajian Tradisi Nyekar di Indonesia - Yunita, Iin; Anisa Dewi Kusumaningrum, Sri; amaya Setya Putri, Lovena T; Lailatusubha, Nur; Lukman Hakim Lac, Muhammad; Muhammad Noor, Aditia (Postmodernism: Indonesian Journal of Multidisciplinary Islamic Studies, 2025)
The cultural practice of cemetery pilgrimage, commonly referred to as nyekar, remains a deeply rooted tradition within Indonesian especially Javanese society. It involves the ritual of scattering flowers over graves while offering collective prayers, serving as a symbolic reminder of human mortality. This study explores the historical origins of the cemetery pilgrimage tradition, examines its interpretation within Islamic perspectives, and analyzes its purposes across different regions in Indonesia. Employing a qualitative research method, the study is based on secondary data obtained from scholarly journals, articles, and other relevant literature. Although the primary data source is textual, the analysis incorporates empirical insights derived from cultural realities observed in society. The findings suggest that nyekar emerged from the cultural interplay between Islamic teachings, Javanese customs, and pre-Islamic (notably Hindu) beliefs. Within Islamic discourse, cemetery visitation was initially prohibited due to associations with pre-Islamic superstitions, but was later permitted and even recommended for its moral and spiritual value. The intentions behind engaging in nyekar vary among individuals, shaped by theological understanding, cultural traditions, and personal motivations.